Ceramic component and method for manufacturing the same

By using block aluminum or aluminum alloy to stack ceramic green sheets to manufacture ceramic components, the high resistance and high cost problems caused by low melting point of copper conductive materials are solved, and the manufacturing of ceramic components with low resistance and high thermal conductivity is achieved, reducing production costs and Improved performance.

CN111446196BActive Publication Date: 2025-01-14SHINKO ELECTRIC IND CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202010004322.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-01-17
Filing Date
2020-01-03
Publication Date
2025-01-14
Estimated Expiration
2040-01-03

AI Technical Summary

Technical Problem

When using copper as a conductive material, the melting point is lower than the degreasing and firing temperature of the ceramic green sheet, resulting in a long processing time and an increase in cost, and the resistance of the conductive material is high.

Method used

Using block aluminum or aluminum alloy as conductive material, ceramic parts are manufactured by laminated with predetermined ceramic green sheets, and the metal film is melted during the firing process to form conductive parts, avoiding long-term degreasing and firing, reducing resistance and improving Thermal conductivity.

Benefits of technology

The resistivity reduction and thermal conductivity improvement of the conductive material are achieved, while avoiding cost increases and the resistivity increase and thermal conductivity reduction caused by internal stress and inclusions are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111446196B_ABST
    Figure CN111446196B_ABST
Patent Text Reader

Abstract

The present invention provides a ceramic component and a manufacturing method thereof, which can avoid cost increase and reduce the resistance of conductive materials. The ceramic component (100) includes a ceramic sintered body (110) and a conductive component (111) of aluminum or aluminum alloy arranged in the sintered body (110).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a ceramic component and a method for manufacturing the same. Background Art

[0002] Composite materials using ceramics and conductive materials have been proposed for electrostatic chucks, wiring substrates, piezoelectric actuators, and the like. The method for manufacturing a composite material of ceramics and conductive materials is as follows. First, a powder of a metal having a melting point higher than the temperature at which the ceramic is fired is made into a paste and applied to the surface of a ceramic green sheet. A plurality of the green sheets are prepared, stacked one on top of the other, and fired in a reducing atmosphere. In this way, a composite material can be manufactured. As metal, tungsten or molybdenum is mainly used. In addition, in Patent Document 1, a method for using copper as a metal to achieve low resistance is proposed.

[0003] Patent Document 1: Japanese Patent Application Laid-Open No. 7-015101

[0004] Patent Document 2: Japanese Patent Application Publication No. 2005-223185

[0005] Patent Document 3: Japanese Patent Application Laid-Open No. 62-260373

[0006] However, since the melting point of copper is significantly lower than the temperature suitable for degreasing and firing of green sheets, when copper is used, the processing will increase the cost such as prolonged degreasing and firing. Summary of the invention

[0007] An object of the present invention is to provide a ceramic component and a method for manufacturing the same, which can avoid cost increase and reduce the resistance of the conductive material.

[0008] According to one aspect of the present disclosure, there is provided a ceramic component including: a sintered body of ceramic; and a conductive component of aluminum or an aluminum alloy disposed in the sintered body.

[0009] According to the disclosed technology, cost increase can be avoided while the resistance of the conductive material can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1A to Figure 1C It is a figure which shows the ceramic component in 1st Embodiment.

[0011] Figure 2A , Figure 2B It is a plan view (part 1) showing the method for manufacturing the ceramic component in the first embodiment.

[0012] Figure 3A , Figure 3B This is a plan view (part 2) showing the method for manufacturing the ceramic component in the first embodiment.

[0013] Figure 4A , Figure 4B This is a plan view (part 3) showing the method for manufacturing the ceramic component in the first embodiment.

[0014] Figure 5A to Figure 5C This is a cross-sectional view (part 1) showing the method for manufacturing the ceramic component in the first embodiment.

[0015] Figure 6A to Figure 6C This is a cross-sectional view (part 2) showing the method for manufacturing the ceramic component in the first embodiment.

[0016] Fig. 7A , Figure 7B This is a plan view (part 1) showing a method for manufacturing a ceramic component in an experiment related to the first embodiment.

[0017] Fig. 8A , Figure 8B This is a plan view (part 2) showing a method for manufacturing a ceramic component in an experiment related to the first embodiment.

[0018] Figures 9A to 9C This is a cross-sectional view (part 1) showing a method for manufacturing a ceramic component in an experiment related to the first embodiment.

[0019] Fig. 10A , Fig. 10B This is a cross-sectional view (part 2) showing a method for manufacturing a ceramic component in an experiment related to the first embodiment.

[0020] Fig.11 It is a cross-sectional view showing an electrostatic chuck in the second embodiment.

[0021] Fig.12 It is a plan view showing an inductor according to the third embodiment.

[0022] The reference numerals are described as follows:

[0023] 1. 101 First Raw Film

[0024] 2.102 Second Raw Film

[0025] 2A, 102A holes

[0026] 3.103 The third raw film

[0027] 10, 110 sintered body

[0028] 11.111 Conductive parts

[0029] 11A Aluminum Foil

[0030] 111A Metal Film

[0031] 200 Electrostatic Chuck

[0032] 300 Inductor DETAILED DESCRIPTION

[0033] As a conductive material with low resistance, the inventors focused on aluminum. However, since the melting point of aluminum is about 660°C and is relatively low, aluminum cannot be used to replace tungsten or molybdenum in the conventional method using a paste of tungsten or molybdenum powder. Therefore, the inventors conducted in-depth research on a method using bulk aluminum. As a result, it was found that by using a predetermined ceramic green sheet, it is possible to appropriately manufacture ceramic parts using bulk aluminum or aluminum alloy.

[0034] Hereinafter, the embodiments will be described in detail with reference to the drawings. It should be noted that in this specification and the drawings, components having substantially the same functional structure are given the same reference numerals and overlapping descriptions may be omitted.

[0035] (First embodiment)

[0036] First, a first embodiment will be described. The first embodiment relates to a ceramic component. Figure 1A to Figure 1C It is a figure which shows the ceramic component in 1st Embodiment. Figure 1A It is a floor plan. Figure 1B It is along Figure 1A The cross-section of line II in Figure 1C It is along Figure 1A Cross-sectional view along line II-II in FIG.

[0037] like Figure 1A to Figure 1C As shown, the ceramic component 100 in the first embodiment includes a ceramic sintered body 110 and a conductive member 111 of aluminum or an aluminum alloy provided in the sintered body 110. In the sintered body 110, a hole 102A reaching the conductive member 111 may be formed.

[0038] In the ceramic component 100 thus configured, the resistivity of the conductive component 111 can be made lower than that of a conductive component formed using a paste of tungsten or molybdenum powder. In addition, the thermal conductivity of the conductive component 111 can be made higher than that of a conductive component formed using a paste of tungsten or molybdenum powder. For example, the resistivity of tungsten is 52.8 nΩm and the thermal conductivity is 173 W / (mK), while the resistivity of aluminum is 28.2 nΩm and the thermal conductivity is 237 W / (mK).

[0039] Furthermore, according to the method which will be described later, the ceramic component 100 can be manufactured without performing long-term degreasing and firing, and an increase in cost can be suppressed.

[0040] The relative density of the sintered body 110 is preferably 90% or more, more preferably 95% or more. If the relative density of the sintered body 110 is less than 90%, continuous pores are likely to form, and aluminum or aluminum alloy, which is the material of the conductive member 111, is easily lost by penetration or vaporization.

[0041] The sintered body 110 is preferably made of a material that is difficult to react chemically with aluminum or an aluminum alloy. For example, the sintered body 110 preferably contains 96% by mass or more of aluminum oxide (Al2O3), and more preferably contains 99% by mass or more of aluminum oxide. Compared with aluminum oxide, silicon oxide (SiO2), magnesium oxide (MgO) and calcium oxide (CaO) are more likely to react chemically with aluminum or an aluminum alloy. Therefore, the total amount of silicon oxide, magnesium oxide and calcium oxide is preferably less than 4% by mass of the sintered body 110, and more preferably less than 1% by mass.

[0042] Next, a method for manufacturing the ceramic component 100 in the first embodiment will be described. Figure 2A to Figure 4B is a plan view showing a method for manufacturing a ceramic component in a first embodiment, Figures 5A to 6C It is a cross-sectional view showing the method for manufacturing the ceramic component in the first embodiment. Figures 5A to 6C Equivalent to Figure 2A to Figure 4B Cross-section along line II in FIG.

[0043] First, if Figure 2A and Figure 5A As shown, a first green sheet 101 is prepared. As the first green sheet 101, for example, a large green sheet from which four ceramic components 100 can be obtained is used. In other words, the first green sheet 101 has four regions in which structures corresponding to the ceramic components 100 are formed. These regions will be divided by cutting along cutting lines 151 later. The same is true for the second green sheet 102 and the third green sheet 103 to be described later. Next, a block-shaped metal film 111A of aluminum or an aluminum alloy is provided on the first green sheet 101. A metal foil can be used as the metal film 111A.

[0044] Afterwards, if Figure 2B and Figure 5B As shown, the second green sheet 102 is provided on the first green sheet 101 , and a hole 102A reaching the metal film 111A is formed in the second green sheet 102 .

[0045] Then, if Figure 3A and Figure 5CAs shown, the third green sheet 103 is provided on the second green sheet 102. The hole 102A is blocked by the third green sheet 103. In this embodiment, the stacked body of the second green sheet 102 and the third green sheet 103 is an example of the second green sheet of the present invention, and the hole 102A is an example of a gap. The gap may be formed on either the first green sheet or the second green sheet, or on both. In either case, the first green sheet and the second green sheet are stacked on each other in such a manner as to block the gap.

[0046] Then, if Figure 3B and Fig. 6A As shown, the first green sheet 101, the second green sheet 102, and the third green sheet 103 are integrated by heating and pressing. Then, sintering is performed to obtain a sintered body 110. During the sintering, the metal film 111A melts and solidifies to obtain the conductive member 111.

[0047] Since the first green sheet 101, the second green sheet 102, and the third green sheet 103 are densified approximately isotropically by firing, the volume of the sintered body 110 is smaller than the total volume of the first green sheet 101, the second green sheet 102, and the third green sheet 103. On the other hand, the volume of the conductive member 111 is equal to the volume of the block-shaped metal film 111A. In the present embodiment, the hole 102A is formed in the second green sheet 102, and the contraction of the sintered body 110 is completed while the metal film 111A is melted. Therefore, a part of the molten metal enters the hole 102A and solidifies. Therefore, it is possible to avoid the generation of internal stress accompanying the contraction of the sintered body 110.

[0048] After sintering, Figure 4A and Figure 6B As shown, the sintered body 110 is ground and polished to expose the hole 102A.

[0049] Then, if Figure 4B and Figure 6C As shown, the sintered body 110 is cut along cutting lines 151 to be individualized.

[0050] In this manner, the ceramic component 100 according to the first embodiment can be manufactured.

[0051] According to this manufacturing method, the conductive member 111 can be obtained from the metal film 111A when the integrated first green sheet 101, the second green sheet 102, and the third green sheet 103 are fired. In other words, there is no need for special treatments such as long-term degreasing and sintering to obtain the conductive member 111. Therefore, it is possible to suppress an increase in manufacturing costs. In addition, since the hole 102A is formed in the second green sheet 102, even if the volume of the ceramic shrinks due to firing, it is possible to avoid the generation of internal stress.

[0052] Furthermore, in the conventional method of using a metal powder paste, inclusions are mixed into the conductive component. In contrast, in the present manufacturing method, since a block-shaped metal film 111A can be used, an increase in resistivity and a decrease in thermal conductivity caused by the mixing of inclusions can be avoided.

[0053] For each of the first green sheet 101 , the second green sheet 102 , and the third green sheet 103 , the ratio of aluminum oxide in the ceramic constituting the green sheet is preferably 96 mass % or more, more preferably 99 mass % or more, in order to suppress chemical reactions between the ceramic and aluminum or aluminum alloy.

[0054] The firing temperature for obtaining the sintered body 110 may be a temperature higher than the melting point of the metal film 111A, and is preferably 700° C. or higher, for example. Although it depends on the materials of the first green sheet 101, the second green sheet 102, and the third green sheet 103, the firing temperature is preferably 1300° C. or higher. In addition, if the firing temperature exceeds 1600° C., a chemical reaction is likely to occur between the molten metal and the ceramic. Therefore, the firing temperature is preferably 1600° C. or lower.

[0055] The firing atmosphere for obtaining the sintered body 110 is preferably an oxidizing atmosphere such as an air atmosphere. A dense oxide film, also called a passivation film, is formed on the surface of solid aluminum or aluminum alloy. However, if aluminum or aluminum alloy is heated above the melting point, the oxide film is broken along with the melting of aluminum or aluminum alloy, and in a vacuum atmosphere or a reducing atmosphere, the molten metal continues to evaporate along with the rise in temperature. In particular, if it is above 1200°C, the vapor pressure rises significantly and the evaporation loss is large. In contrast, in an oxidizing atmosphere such as an air atmosphere, even if the oxide film is broken, a new oxide film will be quickly formed. Therefore, the evaporation loss of aluminum or aluminum alloy can be suppressed.

[0056] In the present embodiment, the destruction and reformation of the oxide film mainly occur at the portion exposed in the hole 102A of the metal film 111A. The larger the range where the oxide film is destroyed and reformed, the greater the oxidation loss of the metal. However, in the present embodiment, since the range where the oxide film is destroyed and reformed is limited, the oxidation loss of aluminum or aluminum alloy can also be suppressed.

[0057] By firing in an air atmosphere, the organic components contained in the first green sheet 101, the second green sheet 102, and the third green sheet 103 can be quickly removed. By removing the organic components, the influence of residual carbon on the ceramic properties can be suppressed. In addition, for firing in an air atmosphere, there is no need for atmosphere control gases such as hydrogen, nitrogen, and ammonia decomposition gas. In addition, compared with a vacuum atmosphere and a reducing atmosphere, an air atmosphere has the advantages of easy management and low equipment cost.

[0058] The number of ceramic components 100 obtained from the stack of the first green sheet 101, the second green sheet 102, and the third green sheet 103 is not limited to 4. For example, one ceramic component 100 may be manufactured without cutting the stack of the first green sheet 101, the second green sheet 102, and the third green sheet 103.

[0059] The hole 102A does not need to be exposed in the ceramic component 100 of the final product, and the user of the ceramic component 100 can form a conductive path with the conductive component 111. Communication can also be performed using capacitance with the conductive component 111. In addition, the hole 102A can be filled with a conductive material or a ceramic material.

[0060] Here, experiments conducted by the present inventors regarding the first embodiment will be described. Figures 7A to 8B It is a plan view showing a method of manufacturing a ceramic component in an experiment related to the first embodiment. Figures 9A to 10B It is a cross-sectional view showing a method of manufacturing a ceramic component in an experiment related to the first embodiment. Figures 9A to 10B Equivalent to Figures 7A to 8B Cross-section along line II in FIG.

[0061] In this experiment, first, Fig. 7A and Fig. 9A As shown, the first green sheet 1 is formed by a doctor blade method. In forming the first green sheet 1, a slurry in which alumina powder with an average particle size of less than 1 μm, polyvinyl butyral, dibutyl phthalate, 2-propanol, and ethyl acetate are mixed by a ball mill is used. The thickness of the first green sheet 1 is about 0.5 mm. The second green sheet 2 and the third green sheet 3 to be described later are also prepared in the same manner, and the thickness thereof is also about 0.5 mm. Next, an aluminum foil 11A with a thickness of about 0.03 mm is provided on the first green sheet 1. The plane shape of the aluminum foil 11A is a rectangle of 30 mm×10 mm.

[0062] Afterwards, if Figure 7B and Fig. 9B As shown, a second green sheet 2 is provided on a first green sheet 1, and holes 2A are formed at two locations in the second green sheet 2 so as to reach the aluminum foil 11. The diameter of the holes is 3 mm.

[0063] Then, if Fig. 8A and Fig. 9C As shown, the third green sheet 3 is disposed on the second green sheet 2 , and the hole 2A is blocked by the third green sheet 3 .

[0064] Then, if Fig. 10AAs shown, the first green sheet 1, the second green sheet 2 and the third green sheet 3 are integrated by heating and pressing, and then fired at 1500° C. in an air atmosphere to obtain a sintered body 10. During the firing, the aluminum foil 11A melts and solidifies to obtain the conductive member 11.

[0065] Then, if Figure 8B and Fig. 10B As shown, the sintered body 10 is ground and polished to expose the holes 2A.

[0066] Then, a two-terminal simple resistance tester having contact resistance was used to measure the resistance of the conductive member 11. The resistance of the conductive member 11 was 0.3 mΩ, which was sufficiently low.

[0067] (Second embodiment)

[0068] Next, a second embodiment will be described. The second embodiment relates to an electrostatic chuck including a ceramic member. Fig.11 It is a cross-sectional view showing an electrostatic chuck in the second embodiment.

[0069] like Fig.11 As shown, the electrostatic chuck 200 in the second embodiment includes a ceramic sintered body 210, an electrostatic electrode 220 of aluminum or aluminum alloy provided in the sintered body 210, and an electrostatic electrode 230 of aluminum or aluminum alloy provided in the sintered body 210. A hole 202A that reaches the electrostatic electrode 220 and a hole 203A that reaches the electrostatic electrode 230 are formed on one surface 210A of the sintered body 210. A through-hole conductor 221 connected to the electrostatic electrode 220 is provided in the hole 202A, and a through-hole conductor 231 connected to the electrostatic electrode 230 is provided in the hole 203A.

[0070] In the electrostatic chuck 200 thus configured, a positive voltage is applied to one of the electrostatic electrodes 220 or 230, and a negative voltage is applied to the other via the through-hole conductors 221 and 231. As a result, the surface 210B opposite to the surface 210A where the holes 202A and 203A are formed is charged, and an object such as a semiconductor wafer is attracted to the surface 210B.

[0071] In the electrostatic chuck 200, the resistivity of the electrostatic electrodes 220 and 230 can be lower than that of the electrostatic electrodes formed using a paste of tungsten or molybdenum powder. In addition, the thermal conductivity of the electrostatic electrodes 220 and 230 can be higher than that of the conductive member formed using a paste of tungsten or molybdenum powder.

[0072] Furthermore, similarly to the ceramic component 100 , the electrostatic chuck 200 can be manufactured without performing long-term degreasing and firing, and cost increase can be suppressed.

[0073] The relative density of the sintered body 210 is preferably 90% or more, more preferably 95% or more. If the relative density of the sintered body 210 is less than 90%, the probability of forming continuous pores becomes high, and the aluminum or aluminum alloy as the material of the electrostatic electrodes 220 and 230 is easily lost by penetration or vaporization.

[0074] The sintered body 210 is preferably made of a material that does not easily react chemically with aluminum or an aluminum alloy. For example, the sintered body 210 preferably contains 96% by mass or more of aluminum oxide, and more preferably contains 99% by mass or more of aluminum oxide.

[0075] When manufacturing the electrostatic chuck 200, for example, a method that imitates the manufacturing method of the ceramic component 100 can be used to grind and polish the sintered body 210 to expose the holes 202A and 203A, and then a through-hole conductor 221 is formed in the hole 202A, and a through-hole conductor 231 is formed in the hole 203A.

[0076] Depending on the size of holes 202A and 203A, aluminum or an aluminum alloy that enters holes 202A and 203A due to volume shrinkage of ceramics and solidifies may also be used as through-hole conductors 221 and 231 .

[0077] (Third embodiment)

[0078] Next, a third embodiment will be described. The third embodiment relates to an inductor including a ceramic component. Fig.12 It is a plan view showing an inductor according to the third embodiment.

[0079] like Fig.12 As shown in FIG. 1 , the inductor 300 in the third embodiment includes a ceramic sintered body 310 and a conductive member 311 of aluminum or aluminum alloy provided in the sintered body 310. The conductive member 311 has a spiral shape in a plan view. A hole 302A reaching one end of the conductive member 311 and a hole 302B reaching the other end of the conductive member 311 are formed on one surface of the sintered body 310.

[0080] The inductor 300 configured in this manner can be electrically connected to an external circuit via the holes 302A and 302B.

[0081] In the inductor 300 , the resistivity of the conductive member 311 can be lower than that of a conductive member formed using a paste of tungsten or molybdenum powder. In addition, the thermal conductivity of the conductive member 311 can be higher than that of a conductive member formed using a paste of tungsten or molybdenum powder.

[0082] Furthermore, similarly to the ceramic component 100 , the inductor 300 can be manufactured without performing long-term degreasing and firing, and cost increase can be suppressed.

[0083] The relative density of the sintered body 310 is preferably 90% or more, more preferably 95% or more. If the relative density of the sintered body 310 is less than 90%, continuous pores are likely to form, and aluminum or aluminum alloy, which is the material of the conductive member 311, is easily lost by penetration or vaporization.

[0084] The sintered body 310 is preferably made of a material that does not easily react chemically with aluminum or an aluminum alloy. For example, the sintered body 310 preferably contains 96% by mass or more of aluminum oxide, and more preferably contains 99% by mass or more of aluminum oxide.

[0085] When manufacturing the inductor 300 , for example, a method similar to the method for manufacturing the ceramic component 100 may be used to grind and polish the sintered body 310 so that the holes 302A and 302B are exposed.

[0086] Although the preferred embodiments and the like have been described in detail above, the present invention is not limited to the above embodiments and the like, and various modifications and substitutions may be made to the above embodiments and the like without departing from the scope described in the claims.

[0087] For example, although the ceramic component is used for an electrostatic chuck in the second embodiment and for an inductor in the third embodiment, the use of the ceramic component is not limited. For example, the ceramic component may be used for a package substrate of a power semiconductor device or the like.

Claims

1. A method for manufacturing a ceramic component, comprising: A step of sandwiching a metal film of aluminum or aluminum alloy between the first green sheet and the second green sheet; as well as a step of firing the first green sheet and the second green sheet at a temperature not lower than the melting point of the metal film to obtain a ceramic sintered body, wherein 96% by mass or more of the ceramic constituting the sintered body is alumina, The relative density of the sintered body is above 90%, A gap is provided at a portion of a surface of the first green sheet or the second green sheet or both of the first green sheet or the second green sheet that contacts the metal film. In the step of obtaining the sintered body, a portion of the melted metal film enters the voids and solidifies.

2. The method for manufacturing a ceramic component according to claim 1, wherein: The calcination is performed in an oxidizing atmosphere.

3. The method for manufacturing a ceramic component according to claim 2, wherein: The calcination is performed in an air atmosphere.

4. The method for producing a ceramic component according to any one of claims 1 to 3, wherein: The sintering is performed at a temperature of 700° C. or higher and 1600° C. or lower.

5. The method for manufacturing a ceramic component according to claim 4, wherein: The sintering is performed at a temperature of 1300° C. or higher and 1600° C. or lower.

Citation Information

Patent Citations

  • Manufacture of laminated type piezoelectric actuator

    JP1987260373A

  • Oxide ceramic circuit board and its manufacture

    JP1995015101A

  • Electrostatic chuck and its manufacturing method

    JP2005223185A

  • Plasma-resistant member

    JP1999278919A